Dynamical behavior and image encryption application of a memristor-based circuit system - Li, Chun-Lai; Li, Zhao-Yu; Feng, Wei; Tong, Yao-Nan; Du, Jian-Rong; Wei, Du-Qu (International journal of electronics and communications, 2019)
Memristive system and encryption technology are two hot topics in the study of nonlinear dynamics. In this paper, we introduce a memristor-based circuit system and conventionally explore its dynamical behavior by analyzing phase portraits, time series, Lyapunov exponents and bifurcation diagrams. It is found that this system exhibits abundant dynamics such as multi-stability, transient dynamics and antimonotonicity. As it is difficult to reproduce the accurate dynamics because of the extremely sensitive dependence on initial conditions and system parameter, and this system can be recommendable for secure encryption application. Consequently, by virtue of the excellent characteristics of the memristive system, we design a chaotic image encryption algorithm based on dynamic DNA operation and dynamic diffusion (CIEA-4D). The pixel updating, permutation, DNA operation and diffusion of the encryption algorithm are all closely related to the plain image, which strongly enhances the security since a tiny change in plain image will influence the whole encryption process. What’s more, the algorithm has a high operational efficiency for the parallel computing of DNA operation, the pre-acquired chaotic sequence and hash values of plaintext images.